Skin microbiota: pathogenic roles and implications in atopic dermatitis - Cong Huang; Cong Huang; Fan Zhuo; Fan Zhuo; Yang Guo; Yang Guo; Yang Guo; Siyu Wang; Siyu Wang; Siyu Wang; Siyu Wang; Kaoyuan Zhang; et al. (Frontiers in Cellular and Infection Microbiology)
Atopic dermatitis (AD) is a chronic and inflammatory skin disorder characterized by impaired barrier function and imbalanced immunity. Recent advances have revealed that dysbiosis of skin microbiota plays important roles in the pathogenesis and development of AD. Meanwhile, endogenous and external factors contribute to the dysbiosis of skin microbiota in AD. Additionally, various treatments, including topical treatments, phototherapy, and systemic biologics, have demonstrated positive impacts on the clinical outcomes, alongside with the modulations of cutaneous microbiota in AD patients. Importantly, therapeutics or products regulating skin microbiota homeostasis have demonstrated potential for AD treatment in early clinical studies. In this review, we underline changes of the skin microbiota correlated with AD. Meanwhile, we provide an overview of the skin microbiota regarding its roles in the pathogenesis and development of AD. Finally, we summarize therapeutic strategies restoring the skin microbial homeostasis in AD management.